2021
DOI: 10.1007/s40121-021-00540-5
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Adherence of Antiretroviral Regimens Containing Long-Acting Fusion Inhibitor Albuvirtide for HIV Post-Exposure Prophylaxis: A Cohort Study in China

Abstract: Introduction: There have been no prospective clinical studies investigating adherence and tolerability of HIV post-exposure prophylaxis (PEP) in China. Tolerability, adherence, and transmitted drug resistance are concerns, especially when single-tablet regimen (STR) usage is low. The present study aimed to explore the safety, tolerability, and adherence of regimens containing albuvirtide (ABT) compared with recommended non-STR antiretrovirals for HIV PEP. Methods: This was a prospective, open-label, multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…AZT/3TC can be used in individuals with decreased renal function and no HBV infection. A study has shown that PEP regimen containing ABT (ABT + DTG, or ABT + TDF + 3TC) had high treatment completion rate, compliance, and good safety, but more researches needed on this regimen [52] …”
Section: Hiv Exposure Management and Prophylaxis[2247–49]mentioning
confidence: 99%
See 1 more Smart Citation
“…AZT/3TC can be used in individuals with decreased renal function and no HBV infection. A study has shown that PEP regimen containing ABT (ABT + DTG, or ABT + TDF + 3TC) had high treatment completion rate, compliance, and good safety, but more researches needed on this regimen [52] …”
Section: Hiv Exposure Management and Prophylaxis[2247–49]mentioning
confidence: 99%
“…A study has shown that PEP regimen containing ABT (ABT + DTG, or ABT + TDF + 3TC) had high treatment completion rate, compliance, and good safety, but more researches needed on this regimen. [52] Timing of PEP initiation and recommended duration: PEP should be initiated as soon as possible after HIV exposure (within 2 hours where possible). It is best to start PEP within 24 hours after exposure, but no later than 72 hours.…”
Section: Principles Of Medication Regimens For Hiv Prophylaxis After ...mentioning
confidence: 99%
“… 26 , 27 The daily cART treatment for mice contains 61.5 mg/kg lamivudine (3TC), 10.25 mg/kg dolutegravir (DTG), and 61.5 mg/kg tenofovir disoproxil fumarates (TDF), equivalent to the combination of 300 mg 3TC/50 mg DTG/300 mg TDF for human. 32 , 33 , 34 The dose of NMN was 300 mg/kg/day for mice, which is equivalent to 25 mg/kg/day for human. 34 , 35 HIV-infected huPBL mice were used for negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The data to support expansion of these newer treatment agents to PEP have increased over time and select STRs have already been incorporated into treatment guidelines in other countries 98 . Finally, future long‐acting ARVs could also play a role in improved adherence to HIV PEP, with an early study showing potential benefit in combination with oral therapy for 28 days 100 . Future long‐acting injectables with the capability to provide one injection for the entirety of PEP therapy should be explored to further enhance adherence.…”
Section: Post‐exposure Prophylaxismentioning
confidence: 99%